REGISTER PETANI KELAPA SAWIT DI DESA MANUNGGUL LAMA KECAMATAN SUNGAI DURIAN KABUPATEN KOTABARU (REGISTER OF PALM OIL FARMERS IN MANUNGGUL LAMA VILLAGE, SUNGAI DURIAN DISTRICT, KOTABARU DISTRICT) - Agnes Erfina Belembele (Universitas Lambung Mangkurat, 2023)
Â AbstractRegister of Palm Oil Farmers in Manunggul Lama Village, Sungai Durian District, Kotabaru District. The meeting of people from different backgrounds in terms of economic and social status comes from the upper middle to lower middle class, of course the language used is also different and gives rise to various variations in the use of language that are unique and interesting. This research uses descriptive qualitative method. The method of collecting data in this study is the listening method with tapping technique as the basic technique and the listening technique involving proficient and note-taking technique as a follow-up technique. The method of data analysis in this study is the translational equivalent method and the pragmatic equivalent method. Presentation of the results of data analysis using informal methods. The results showed that: 1) the registers of oil palm farmers in Manunggul Lama Village, Sungai Durian District, Kotabaru Regency have word and phrase forms, then the characterized register forms consist of elliptical features, special word characteristics, and shortening/alegro characteristics, 2) Types registers of oil palm farmers in Manunggul Lama Village, Sungai Durian District, Kotabaru Regency, namely the type of business or consultative register, the type of casual or casual register, and the type of intimate or intimate register. 3) Changes in the meaning of the register of oil palm smallholders in Manunggul Lama Village, Sungai Durian District, Kotabaru Regency, namely changes in meaning caused by the environment, changes in meaning caused by combinations of words, and changes in meaning due to associations.Keywords:Â Register, Oil Palm, Manunggul Lama Village.AbstrakRegister Petani Kelapa Sawit di Desa Manunggul Lama Kecamatan Sungai Durian Kabupaten Kotabaru. Pertemuan masyarakat dari latar belakang yang berbeda ditinjau dari segi ekonomi dan status sosial yang berasal dari menengah atas sampai menengah bawah tentu bahasa yang digunakan juga berbeda dan memunculkan berbagai variasi pemakaian bahasa yang unik dan menarik. Penelitian ini menggunakan metode kualitatif deskriptif. Metode pengumpulan data dalam penelitian ini adalah metode simak dengan teknik sadap sebagai teknik dasar dan teknik simak libat cakap serta teknik catat sebagai teknik lanjutannya. Metode analisis data dalam penelitian ini adalah metode padan translasional dan metode padan pragmatis. Penyajian hasil analisis data dengan menggunakan metode informal. Hasil penelitian menunjukkan bahwa: 1) register petani kelapa sawit di Desa Manunggul Lama Kecamatan Sungai Durian Kabupaten Kotabaru memiliki bentuk kata dan frasa, selanjutnya bentuk register berciri terdiri atas berciri elips, berciri kata khusus, dan berciri pemendekan/alegro, 2) Jenis-jenis register petani kelapa sawit di Desa Manunggul Lama Kecamatan Sungai Durian Kabupaten Kotabaru yaitu jenis register usaha atau consultative, jenis register santai atau casual, dan jenis register intim atau intimate. 3) Perubahan makna register petani kelapa sawit di Desa Manunggul Lama Kecamatan Sungai Durian Kabupaten Kotabaru yaitu perubahan makna yang disebabkan oleh lingkungan, perubahan makna yang disebabkan karena adanya gabungan kata, dan perubahan makna karena perkumpulan/asosiasi.Kata-kata kunci: Register, Kelapa Sawit, Desa Manunggul Lama